Development of Augmented Reality (Ar) Learning Media of Natural Science Subject on Subject Matter of Water Cycle for MI Grade V Students - Istiningsih Istiningsih; Fajar Dwi Mukti; Edy Yusuf Nur Samsu Santoso (Program Studi Pendidikan Guru Madrasah Ibtidaiyah, 2020)
This development research aims to: (1) produce the learning medium of Augmented Reality (AR) on natural science subject on subject water recycle in class V MI Wahid Hasyim; (2) knowing the quality of the products the learning medium of Augmented Reality (AR) on natural science subject on subject matter of water recycle ; (3) find out the results of the response of teachers and students so that decent media used in learning the natural science.The development model used in this medium is the modified Thiagarajan 4D model. The stages carried out consist of three stages, namely Define (defining), Design (design), and Develop (development). The media for learning Augmented Reality (AR) was assessed by 1 media expert, 1 matter expert, 1 peer reviewer, 1 class V teacher and 10 V grade students MI Wahid Hasyim to find out student responses. The instruments used were questionnaire and evaluation sheets using non-objective description forms for testing the quality of science learning media products. The results of the study are: (1) Augmented Reality (AR) media learning products have been developed for water cycle matter run on Android version 4.1 jelly bean, (2) Learning media for Augmented Reality (AR) water cycle matter with feasibility according to the overall assessment of reviewers and peers reviewers obtain very good quality ie 90.2%, (3) response or response of class V teachers is very good with a percentage of 82.57%. Likewise, the students' responses obtained a percentage of 90.2% with a positive response so that the learning media had a quality category on the Very Good criteria which was also supported by the results of students who experienced an increase of 35.8%. Based on the results of data acquisition shows that the learning media of Augmented Reality (AR) on natural science subjects water cycle matter in class V MI Wahid Hasyim is worthy of being used as a learning resource for students.